Políticas nacionales para el control del VIH y la evolución de la epidemia en México: un análisis de 1990 a 2017. - Ryo Shiba-Matsumoto, Andrey; Bravo-García, Enrique; Salvador Sánchez-Domínguez, Mario; Magis-Rodríguez, Carlos; Gómez-Dantés, Héctor (Salud Pública de México)
Objective. To analyze the changes in the burden of HIV disease in the period 1990-2017, in contrast to the intervention policies and programs implemented for its prevention and control. Materials and methods. A timeline of policies and interventions in Mexico was developed and with JoinPoint regression models, we analyzed their possible relationship with significant changes in trends in the burden of HIV disease. Results. Changes in the burden of disease are related to the universalization of access to antiretroviral drugs (ARV), comprehensive care programs, and the fight against stigma and discrimination. In the period analyzed, there is a decrease in mortality related to universal and free access to ARVs. The magnitude of the changes tends to be greater in men than in women. Conclusions. The policies and programs implemented to treat people with HIV/AIDS in Mexico were integrated into increasingly cohesive and effective strategies.